(untitled) (International Seven Journal of Multidisciplinary, 2023)
The launch of new products represents a critical stage in organizational growth and competitive strategy, as it determines market acceptance, brand positioning, and long-term performance. This article examines the role of marketing in the successful introduction of new products, emphasizing its strategic and operational contributions throughout the launch process. Drawing on established marketing theories and empirical studies, the discussion highlights how market research, segmentation, positioning, and integrated communication reduce uncertainty and enhance consumer adoption. In addition, the article reflects on professional experiences in product launch activities, illustrating how customer-oriented strategies, cross-functional coordination, and data-driven decision-making contribute to improved launch outcomes. The analysis demonstrates that effective marketing acts as a bridge between innovation and the market, transforming technical solutions into value propositions that resonate with consumers and support sustainable competitive advantage.